Determination of Vitamin C Red Guava (Psidium Guajava Linn) Fruit Juice, with Variation of Beverage Packaging - Lubis, Novriyanti; Septiani, Wulan; Abdillah, Muhammad Nur; Prasetiawati, Riska; Junaedi, Effan Cahyati (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The quantitative analysis of vitamin C content from variations beverage packaging containing red guava (Psidium Guajava Linn) fruit juice had been done. In this study, 4 samples were obtained from the shopping center in Garut and Bandung City. Samples were tested quantitatively by 2,6-dichlorophenol indophenol titration method. The results showed different concentration of 4 samples consist of tetra pack packaging, tin, glass, and plastic bottles, such as; 17.99 mg/100 gr, 31.46 mg/100 gr, 13.00 mg/100 gr, and 12.01 mg/100 gr, respectively. These result indicated that the packaging variations affected to the level of vitamin C content which was characterized by decreased levels of vitamin C. It means the levels of vitamin C from this research were not in accordance to nutritional value information on the packaging. Tetra pack packaging was the most stable compared to other packaging even though it had a shorter expired date than with other.